Stereoacuity of Black-White and Red-Green Patterns in Individuals with and without Color Deficiency - Ying Sun; Huang Wu; Yinghong Qiu; Zhiqiang Yue (Journal of Ophthalmology)
Background. Chromatic contrast may affect stereopsis. Daltonism is a common color deficiency in which the colors red and green are incorrectly detected. The aim of this study was to evaluate the stereoacuity of color-defective individuals presented with color symbols that they see defectively. Methods. Ten students diagnosed with daltonism and 10 students with normal color vision were recruited. A stereopsis test system using a phoropter and two 4K smartphones was used. Contour-based graphs and random-dot graphs with black versus white and red versus green patterns were used as test symbols. The Wilcoxon signed rank test was used to test the difference between groups. Results. No significant difference in stereoacuity was found between contour-based and random-dot graphs within both daltonism cohort and normal color vision cohort (P>0.05). A significant difference in stereoacuity was found between the black-white (P=0.005) and red-green (P=0.007) graphs for the daltonism cohort, while no significant difference in stereoacuity was found for the normal color vision cohort (P>0.05). Conclusion. Chromatic contrast is an influential factor for stereopsis measurement in individuals with color deficiency.